Economic Evaluation of an Intervention Promoting Adoption of Occupational Sun Protection Policies. Issue 12 (December 2019) - Meenan, Richard T.; Walkosz, Barbara J.; Buller, David B.; Eye, Rachel; Buller, Mary K.; Wallis, Allan D.; Olivas, Savanna
Abstract : Objective: Economic evaluation of an intervention promoting adoption of occupational sun protection actions by Colorado public sector employers. Methods: Randomized controlled trial with 2-year follow-up conducted during 2010 to 2013. Thirty-three intervention and 30 attention–control worksites in final economic sample. Twenty-four-month intervention of personal contacts, training, and materials. Intervention delivery micro-costed. Costs of implemented actions from employer self-report. Results: Twenty-four-month intervention costs: $121, 789, 51.8% incurred by project staff (per-worksite mean=$1, 732). Worksite costs: $58, 631 (mean = $1, 777). Per-employee costs: $118 project staff, $56 worksites. Materials cost: $5990 (mean = $181). Intervention worksites implemented 72 nontraining sun protection actions post-Sun Safe Workplaces (SSW) (mean = 2.18). Control worksites implemented 39 actions (mean = 1.30). Total costs to intervention worksites of implementing the 72 post-SSW actions: $90, 645 (mean = $2, 747). Control worksite costs: $66, 467 (mean = $2, 216). Per-employee implementation costs are comparable to other worksite health interventions. Conclusion: SSW expanded adoption of sun protection actions at a reasonable per-employee cost.